Zanubrutinib for treatment‐naïve and relapsed/refractory chronic lymphocytic leukaemia: long‐term follow‐up of the phase I/II AU‐003 study. (16th December 2021) - Cull, Gavin; Burger, Jan A.; Opat, Stephen; Gottlieb, David; Verner, Emma; Trotman, Judith; Marlton, Paula; Munoz, Javier; Johnston, Patrick; Simpson, David; Stern, Jennifer C.; Prathikanti, Radha; et al.
Summary: The phase I/II AU‐003 study in patients with treatment‐naïve (TN) or relapsed/refractory (R/R) chronic lymphocytic leukaemia/small lymphocytic lymphoma demonstrated that zanubrutinib therapy results in clinically meaningful and durable responses with acceptable safety and tolerability. We report updated safety and efficacy data for 123 patients with a median follow‐up of 47·2 months. Patients received zanubrutinib 160 mg twice daily (81 patients), 320 mg once daily (40), or 160 mg once daily (two). Discontinuations due to adverse events or disease progression were uncommon. The overall response rate (ORR) was 95·9% (TN, 100%; R/R, 95%) with 18·7% achieving complete response (CR). Ongoing response at 3 years was reported in 85·7%. The ORR in patients with del(17p)/tumour protein p53 mutation was 87·5% (CR 16·7%). The 2‐ and 3‐year progression‐free survival estimates were 90% (TN, 90%; R/R, 91%) and 83% (TN, 81%; R/R, 83%) respectively. The most reported Grade ≥3 adverse events were neutropenia (15·4%), pneumonia (9·8%), hypertension (8·9%) and anaemia (6·5%). The annual incidence of atrial fibrillation, major haemorrhage, Grade ≥3 neutropenia and Grade ≥3 infection decreased over time. With a median follow‐up of ~4 years, responses remain clinically meaningful and durable and long‐term tolerability to zanubrutinib therapy continues.